Sealing of pulp chamber dentin in endodontics: Influence of bond strategy and time‑point application - Puetate, Cristian Fernando Sanchez [UNESP]; Girotto, Aline Carvalho [UNESP]; Zaniboni, Joissi Ferrari [UNESP]; Gelio, Mariana Bena [UNESP]; Besegato, João Felipe; Kuga, Milton Carlos [UNESP] (Wolters Kluwer, 2024)
Context: Seal the dentin of the pulp chamber during endodontic treatment to avoid interfering with the restorative treatment performed afterward. Aims: The aim was to evaluate the effect of three adhesive systems applied in different bonding strategies (etch‑and‑rinse, self‑etch, and universal adhesive) and time‑point application (immediately after the cavity access preparation or after endodontic obturation) on the hybrid layer formation and dentinal penetrability. Materials and Methods: Forty‑eight sound molars were randomly distributed into six groups (n = 10) according to the adhesive system used: Forty‑eight sound molars were randomly distributed into six groups (n = 10) according to the adhesive system used and the time‑point application: Adper Scotchbond Multi‑purpose (AS), Clearfil SE (CF) and Scotchbond Universal (SU) in strategy of immediate endodontic sealing (IES) or delayed endodontic sealing (DES). In IES‑AS, IES‑CF, and IES‑SU groups, dentin sealing was performed immediately after the cavity access, while in DES‑AS, DES‑CF, and DES‑SU, after root canal obturation. The specimens were sectioned in the long axis, in a buccal‑lingual direction, and the dentinal penetrability of the adhesive systems was evaluated using confocal microscopy images. Hybrid layer formation was analyzed by scanning electron microscopy images. Statistical Analysis Used: Dentinal penetrability data were analyzed with the ANOVA test and the Kruskal–Wallis test was performed for hybrid layer data (α = 0.05). Results: IES‑CF showed the lowest dentinal penetrability (P < 0.05), while the other protocols were similar to each other (P > 0.05). No significant differences were found between groups regarding the hybrid layer formation (P > 0.05). Immediate and DES protocols do not influence the hybrid layer formation, regardless of the bond strategy used. Conclusions: Sealing the pulp chamber dentin before endodontic treatment can improve the bond strength of the final restoration but the formation of the hybrid layer was not influenced by the bond strategy.
Keywords: Adhesive system; endodontic irrigation; endodontic treatment; immediate dentin sealing; sodium hypochlorite